Role of Lactobacillus plantarum 299v versus Placebo in symptomatic improvement of irritable bowel syndrome patients - Moeen-Ul-Haq; Ahmad Nawaz Babar; Muhammad Kamran Hassan; Fazl Ullah; Anwar Ullah (Journal of the Pakistan Medical Association, 2022)
Objective: To find the efficacy of lactobacillus plantarum 299v compared to placebo in symptomatic improvement of irritable bowel syndrome patients. Method: The randomised control trial was conducted at the Lady Reading Hospital, Peshawar, Pakistan, from July 20, 2014, to January 20, 2015, and comprised irritable bowel syndrome patients who were randomised into intervention group A treated with lactobacillus plantarum 299v and control group B treated with placebo. Symptoms, like abdominal pain, bloating and complete rectal emptying, were noted and compared between the groups. Data was analysed using SPSS 19. Results: Of the 190 patients assessed, 120(63%) were included; 60(50%) in each of the two groups. After loss to follow-up, the study was completed by 55(91.7%) in group A and 53(88.3%) in group B. The mean age in group A was 37.53 ± 9.02 and it was 34.40±11.23 in group B (p=0.652). The male-to-female ratio and irritable bowel syndrome type in both the groups was not significantly different (p>0.055). There was no significant difference in terms of relieving abdominal pain, bloating and rectal emptying between the groups (p>0.05). Conclusion: No significant efficacy was established in favour of treating in irritable bowel syndrome with lactobacillus plantarum 299v. Trials Registration: Registration number IRCT20200504047303N1 Key Words: IBS, Lactobacillus plantarum 299v, Placebo.